Antimicrobial prescription at the time of discharge from a tertiary-care hospital in India: A potential target for reducing use at the community level. Issue 1 (9th December 2022) - Gupta, Stuti; Gunjiyal, Jacinta; Varma, Sharin; Malhotra, Rajesh; Shrivastav, Sharad; Parveen, Rasna; Mathur, Purva
Abstract: We evaluated the appropriateness of antibiotic prescriptions at discharge from a tertiary-care hospital in India. Of the 790 adult patients included, 84.4% received antibiotics. Microbiological specimens were taken from 67.3% of these patients, and pathogens were identified in 28.8% of cases. Overuse of antimicrobials at hospital discharge should be curtailed.